2012
DOI: 10.4103/1817-1745.106485
|View full text |Cite
|
Sign up to set email alerts
|

Sacrococcygeal myxopapillary ependymoma with anaplastic ependymoma component in an infant

Abstract: Sacrococcygeal location of myxopapillary ependymoma (MPE) is uncommon. Local recurrence and metastases are on record inspite of its benign characteristics. We report a rare case of sacrococcygeal MPE in an 11-month-old female child who showed typical myxopapillary ependymal histology along with anaplastic ependymal component. Ki-67 labeling index in the myxopapillary component was 4-5% and in the anaplastic component was 70%. Six weeks after gross total resection of the tumor, the child presented with local re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…Anaplasia within MPEs has been described as exceptional. Only five have been reported in the literature to our knowledge, most occurring within the pediatric setting with ages ranging from 7 months to 15 years and one occurring in an adult at 38 years of age . Two cases were intradural, two were subcutaneous sacrococcygeal lesions and one was anaplastic at the time of metastasis to an inguinal lymph node .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anaplasia within MPEs has been described as exceptional. Only five have been reported in the literature to our knowledge, most occurring within the pediatric setting with ages ranging from 7 months to 15 years and one occurring in an adult at 38 years of age . Two cases were intradural, two were subcutaneous sacrococcygeal lesions and one was anaplastic at the time of metastasis to an inguinal lymph node .…”
Section: Introductionmentioning
confidence: 99%
“…Only five have been reported in the literature to our knowledge, most occurring within the pediatric setting with ages ranging from 7 months to 15 years and one occurring in an adult at 38 years of age . Two cases were intradural, two were subcutaneous sacrococcygeal lesions and one was anaplastic at the time of metastasis to an inguinal lymph node . Malignant features included punctate necrosis, microvascular proliferation (MVP), increased Ki‐67 LI (80%, 70%, 40% and 10% respectively) and increased mitotic activity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anaplasia in myxopapillary ependymomas is extremely rare, with less than 10 reported cases in the literature. If only subcutaneous myxopapillary ependymomas are considered, there are only two reported cases 10 11. The presence of both anaplastic features and the rosette pattern (which corresponds to ependymoblastic differentiation) put this tumour into the WHO grade IV category.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study on 23 evaluable patients with ESE, Helwig [16] found that 4 (17%) developed metastases; the youngest of these patients, a 17-year-old female, underwent surgical excision of the primary tumor, but developed pleural and lung dissemination 6 months later and died 5 years after her diagnosis. There are another three reports [30][31][32] of children aged 18 months, 11 months, and 4 years whose ESE metastasized to the inguinal lymph nodes: one of them had a component of anaplastic ependymoma but surgery alone achieved a CCR, and a 4-year-old child experienced a lung relapse 19 years after diagnosis and was treated with surgery, achieving a CR at 1 year. Another report [33] described a 10year-old child with multifocal localizations (in the pilonidal area and left buttock), who achieved CR after surgical excision alone.…”
Section: Managementmentioning
confidence: 99%